Chordoma: Immunohistochemical Analysis of Brachury - Sun, H. Ibrahim; Guduk, Mustafa; Gucyetmez, Bulent; Yapicier, Ozlem; Pamir, M. Necmettin (TURKISH NEUROSURGICAL SOC, 2018)
AIM: Chordomas are rare, slow growing but locally aggressive malignancies of the axial skeleton. Skull base chordomas, due to their intricate anatomical localization, pose significant challenges to managing physicians. In classical and chondroid chordomas, the disease course cannot be reliably determined using only morphological criteria. Brachyury (T Gene) was shown to play a central role in chordoma pathogenesis and several studies also showed that this gene also carries potential as a prognostic biomarker. This study aims to correlate Brachyury expression with the clinical course in surgically treated skull base chordomas. MATERIAL and METHODS: Chordoma tumor samples from 14 patients with skull base chordomas, diagnosed using histopathological and immunohistochemistry criteria (epithelial membrane antigen (EMA), S100, pan cytokeratin (panCK)) were retrospectively analyzed for Brachyury expression using immunohistochemistry. Brachyury expression was graded using a 4 point semi-quantitative scoring system. Focal (grade II) and diffuse staining (grade III) were considered as overexpression. Patient recurrence-free survival and total survival were compared between Brachyury overexpressing and non-overexpressing groups using Kaplan-Meier survival analysis. RESULTS: Among the stained tumor samples, 85.7\% were positive for brachyury expression. In both groups, there was one sample that was negative. We did not observe any significant difference among the groups for staining, grade and percentage of brachyury positive cells. CONCLUSION: Brachyury expression in tumor samples is not a sensitive indicator of prognosis in chordomas.
Keywords: Chordoma; Brachyury; Microsurgery; Immunohistochemistry